ANALISIS RATIO LAPORAN KEUANGAN PERUSAHAAN DAGANG MENGGUNAKAN ZAHIR ACCOUNTING VERSI 5.1 - Ela Revita, Maria Lapriska Dian; Rahmayani, Fanny; Ariyati, Indah (Fundamental Management Journal, 2019)
The role of information technology is very important because the existence of information technology can facilitate operations in their business fields. One of the information that is needed by the company is financial report to find out how the company is developing. The financial statements are information used by management for the decision making of the Bekasi Amanah Telaga Harapan Cooperative having its address at Danau Duta Utara Blok D1, Harapan Baru Sub-District, North Bekasi District. Currently the Amanah Telaga Harapan Bekasi Cooperative in making financial reports for the period every month is still manua.. The computerized system is able to produce more precise and accurate information to help smooth daily work. By using the zahir accountuing application version 5.1, companies can easily and quickly obtain Financial Statements and Financial Statement Analysis that are beneficial to the company and its business management and face competition. By analyzing the financial statements the company can identify some of the company's financial strengths and weaknesses. Financial Statement Analysis is also useful as a tool for predicting / estimating assets, debt, capital, cash flow, profit sharing in the future, and predicting the bankruptcy of a company in the future. The use of this application program can be beneficial for the company, so the company can evaluate the financial position and financial performance of the company so that it can improve services to members of the cooperative, related parties, determine corrective measures so you can win the competition and make the best profit. Keywords: Financial Statement Analysis, Trading Companies, Zahir Accounting